The Dimensions of Ruminative Thinking: One for All or All for One. (June 2019) - Mihić, Ljiljana; Novović, Zdenka; Lazić, Milica; Dozois, David J. A.; Belopavlović, Radomir
The Ruminative Thought Scale (RTS) was developed to measure the ruminative thinking style, presumably common to various psychopathological disorders. However, prior factor-analytic research was inconclusive regarding unidimensionality versus multidimensionality of the RTS. The present study was conducted on a large, heterogeneous Serbian sample ( N = 838). A subsample was retested 6 months later providing information about symptoms of depression and various anxiety symptoms. Results showed that a bifactor model of the RTS (representing one general and four group factors) had a better fit than the second-order and one-factor models. The subscale scores were not prospective predictors of symptoms of depression and anxiety, over and above the contribution of the total score. The RTS is a reliable transdiagnostic measure of repetitive thinking. Although there is some clustering of more homogeneous items, there is not enough evidence to support interpretation of the subscales.